Quality Analysis of Black tea Products Using Fisbone Diagram and Failure Mode and Effect Analysis (FMEA) at PT XYZ - Mubarok, Alvian Alvin (Journal of International Conference Proceedings, 2022)
The purpose of this study was to determine the factors that affect the quality of black tea products. This study shows that PT XYZ as a black tea processing company has problems in achieving product quality. This is shown by not achieving the quality target of black tea products, even though the raw materials are relatively in accordance with standards. The analysis used is a cause and effect analysis using a fishbone diagram to determine the causes of product quality problems, as well as the use of pareto analysis and 5-why as a support. Failure mode and effect analysis (FMEA) is used as a tool to mitigate risks resulting from failure of the production process, the results of which are used for suggested improvements. The results of this study indicate that the factors that influence the quality problems of black tea products include the degree of shoot wilt that does not comply with standards, employees who do not comply with the SOP and the problem of the machine being off during the production process. From these problems, the researcher proposes improvements, namely to tighten the supervisory function in the withering division, improve the supervision system and conduct recruitment or training in the machine maintenance division Keywords: Quality, Black Tea, Fishbone Diagram, Pareto Diagram, 5-Why’s Analysis and FMEA